Analisis Unsur Berpikir Kreatif Dan Keterampilan Proses Pada Buku IPAS Muatan IPA Kelas IV Fase B Kurikulum Merdeka: Analisis Unsur Berpikir Kreatif Dan Keterampilan Proses Pada Buku IPAS Muatan IPA Kelas IV Fase B Kurikulum Merdeka - Okdiansyah; Endang Widi Winarni; Abdul Muktadir (Jurnal Kajian Pendidikan Dasar, 2024)
This study aims to describe the emergence of creative thinking elements and process skills in the student handbook of the Natural Sciences subject of the Natural Sciences content. The type of research used is descriptive qualitative. This study uses data analysis techniques using the content analysis method. The results of the study show that: (1) Fluency of thinking (fluency) the emergence of descriptor 1 is 21 occurrences, the emergence of descriptor 2 is 3 occurrences. (2) Flexibility of thinking (flexibility) the emergence of descriptor 1 is 47 occurrences, the emergence of descriptor 2 is 2 occurrences. (3) Original thinking (originality) the emergence of descriptor 1 is 12 occurrences. (4) Process skills observe the occurrence of descriptor 1 as many as 7 occurrences and descriptor 2 as many as 23. Questioning and predicting the occurrence of descriptor 1 as many as 31 occurrences and descriptor 2 as many as 36 occurrences. Planning and conducting investigations of the occurrence of descriptor 1 as many as 30 occurrences and descriptor 2 as many as 23 occurrences. Processing, analyzing data and information organizing data in the form of presenting data identifying patterns of occurrence of descriptor 1 as many as 18 occurrences and descriptor 2 as many as 2 occurrences, Evaluating and reflecting on the occurrence of descriptor 1 as many as 24 occurrences and descriptor 2 no occurrences, and Communicating the results of the occurrence of descriptor 1 10 occurrences and descriptor 2 as many as 27 occurrences.